Addictions counseling today substances and addictive behaviors - Alderson, Kevin (SAGE Publications, Inc., 2020)
"Addictions Counseling Today covers the range of addictions from alcohol, drug abuse, and nicotine to various process addictions including sex, Internet, gaming, social media, and gambling. It includes the various theories and models of addiction as well as a special chapter on the neuroscience of addiction. The book focuses on the DSM-5 classifications for addiction and will include a number of unique features, including Challenging Your Assumptions, Personal Reflections, Counseling Scenarios, and numerous exercises. With an emphasis on CACREP and a number of useful appendices including handouts for role play scenarios, special case studies, personal functioning questionnaires and relaxation techniques, this text is an essential reference for any substance use or addictions counselor"--